Health status of child laborers in Nepal - Joshi, Sunil Kumar; Shrestha, Suvash; Shrestha, Resha; Vaidya, Subhadra (International Journal of Occupational Safety and Health, 2012)
Background Addressing child labor involves ensuring good health of existing child laborers in addition to reducing their number. Objective To determine different physical and psychological health problems among child laborers in Nepal. Methods and material This study compares the status of health between Nepalese child laborers and school going children of similar age. Nineteen different kinds of labors were selected and the child laborers in those work sectors were included in the study. Two medical doctors examined the children individually, and a psychologist assessed the level of stress indicators among the child laborers. Thus, clinical and psychological assessment were done, and compared with the same among school going children. Results A total of 313 child laborers and 200 school children were included in the study. Most of the laborers (82, 26.2%) were engaged in overland transportation and vehicle repair works. Child workers had significantly poor health status than the school going children, in term of pallor, absence of BCG vaccination, lack of de-worming, dermatitis, discharge from eyes, and ear – nose – throat problems. Two hundred eighty eight (92.1%) of the child workers had at least one psychological stress symptom. Conclusions The health status of child laborers is not satisfactory. Thus, measures to ensure quality health should receive priority while addressing child labor. DOI: http://dx.doi.org/10.3126/ijosh.v2i1.5918 International Journal of Occupational Safety and Health, Vol. 2 No. 1 (2012) 31-38